Divine and human violence and destruction in Jeremiah 20:7-13 - Snyman, SD (Acta Theologica, 1999)
Jeremiah 20:7-13 is a text presenting the interpreter with a multitude of problems. Five main areas of research are briefly highlighted. This paper focuses on the interpretation of hamas wasod in Jer 20:8. Eight different interpretations have been offered but no conclusive answer to the exact meaning of the phrase has been given yet. It is argued that due to the ambiguity and structural features of the text the prophet experienced violence and destruction from the divine side as well as from a human side.